Systemic Lupus Erythematosus and Fatigue - Elera-Fitzcarrald, Claudia (2022)
Systemic Lupus Erythematosus (SLE) is a chronic inflammatory autoimmune being fatigue one of its more frequent symptoms. The etiology of this is multifactorial, there are factors related to the disease itself, lifestyles, comorbidities and treatment that are associated. Also, there are several factors to measure it, being the most used instruments: Visual Analog Scale (VAS), "Krupp Fatigue Severity Scale" (FSS) and the "Functional Assessment of Chronic Illness Therapy Fatigue" (FACIT-Fatigue). The impact of fatigue on the SLE patient is important because it affects the patient's quality of life.